The role of football as a super-spreading event in the SARS-CoV-2 pandemic - Ruiz-Lozano, R. E.; Cardenas-De La Garza, J. A.; Ibarra-Nava, I.; Garza-Garza, L. A.; Hernández-Camarena, J. C. (The Journal of Sports Medicine and Physical Fitness, 2020)
LETTERS TO THE EDITOR Super-spreading events (SSEs) are those associated with both an explosive growth early in an outbreak and perpetuated transmis-sion. In SSEs, a single person can infect a disproportionate amount of people. Previous Coronavirus outbreaks, such as the 2003 SARS-CoV and 2015 MERS-CoV outbreaks, were exacerbated by this phenomenon.1 The highly contagious agent SARS-CoV-2 has rapidly created new epicenters across the globe, particularly in Europe and the United States. On March 11, the ongoing spread of SARS-CoV-2 drove the World Health Organization (WHO) to declare COVID-19 a pandemic and global health emergency and urged nations to implement extreme measures to contain it. Football, the most practiced sport worldwide, gathers thousands of people and thus, football events act as SSE. On March 17, for the first time in sixty years, the European Football Championship (EFC), organized by the Union of European Football Association (UEFA), was rescheduled for next year. Football events as SSEs require strict measures to slow down the spread of COVID-19 and to improve public health.